2021
DOI: 10.1007/s10198-020-01247-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization and associated cost of patients with bone metastases from solid tumors who are naïve to bone-targeting agents: a comparative analysis of patients with and without skeletal-related events

Abstract: Background This study analyzes the impact of skeletal-related events (SRE) on healthcare resource utilization (HCRU) and costs incurred by patients with bone metastases (BM) from solid tumors (ST), who are therapy-naïve to bone targeting agents (BTAs). Methods German claims data from 01/01/2010 to 30/06/2018 were used to conduct a retrospective comparative cohort analysis of BTA-naive patients with a BM diagnosis and preceding ST diagnosis. HCRU and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Finally, this study used a regional claims dataset from AOK PLUS, and, therefore, the applicability of the results to the whole of Germany could be limited. However, several previous retrospective studies [32,33] using AOK PLUS claims data confirmed that although patient characteristics may not exactly reflect the country average, the uniform treatment rules observed throughout the country make the AOK PLUS database useful for understanding the economic burden of diseases with a high level of generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study used a regional claims dataset from AOK PLUS, and, therefore, the applicability of the results to the whole of Germany could be limited. However, several previous retrospective studies [32,33] using AOK PLUS claims data confirmed that although patient characteristics may not exactly reflect the country average, the uniform treatment rules observed throughout the country make the AOK PLUS database useful for understanding the economic burden of diseases with a high level of generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Published cost-of-illness studies and surveys indicate that the proportion of out-patient treatments in Germany is 50-60% (15,16,23,27) with no significant difference between German general hospitals, practices, and university hospitals (15). However, these studies assessed bone metastases in general (including complicated bone metastases, patients receiving post-operative radiation for spinal metastases, sometimes with pronounced neurological symptoms), while our patient population (uncomplicated bone metastases) is less likely to require in-patient treatment.…”
Section: Costsmentioning
confidence: 99%
“…Costs associated with a pathological fracture were extracted from a retrospective cost-of-illness study based on German claims data including 2434 patients with bone metastases and solid tumours (23). These costs included in-and out-patient consultations, rehabilitation, out-patient prescriptions, aids, and remedies (23). Costs were adjusted for inflation to the target year 2021 based on the harmonized index of consumer price (32).…”
Section: Costsmentioning
confidence: 99%
“…Moreover, patients with PCa are at a high risk of bone-related complications such as pathological fracture, painful bone lesions requiring surgery or radiation, or spinal cord compression, collectively referred to as skeletal-related events [SREs] [ 15 ]. SREs are sentinel events that cause pain, impair quality of life, function, and survival, and increase healthcare utilization [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%